2013
DOI: 10.1093/aob/mct122
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, controlled-environment seedling root screen for wheat correlates well with rooting depths at vegetative, but not reproductive, stages at two field sites

Abstract: The seedling screen was fast, repeatable and reliable for selecting lines with greater total root length in the young vegetative phase in the field. Lack of significant correlation with reproductive stage root system depth at the field sites used in this study reflected factors not captured in the screen such as time, soil properties, climate variation and plant phenology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 41 publications
4
143
2
1
Order By: Relevance
“…When the root growth of vigorous and non-vigorous wheat genotypes was compared in rhizoboxes by Liao, Palta and Fillery [12], visual differences in root length and proliferation from the one-leaf stage (10 DAS) were monitored, but it was not until the onset of stem elongation (30 DAS) that significant differences occurred. These findings not only reflect the plasticity of the wheat root system when different cultivars are grown under different conditions [2,15,[38][39][40][41][42][43], but uncover the perils of conducting early-stage root phenotyping in wheat [44,45]. Despite the high plasticity of the root system, wheat cultivars, when grown in the field or in rhizoboxes, maintained a similar ranking in root biomass and root length density under well-watered and moderate water deficit conditions [1,46].…”
Section: Characterising the Root Systems Of Cultivars With Contrastinmentioning
confidence: 80%
“…When the root growth of vigorous and non-vigorous wheat genotypes was compared in rhizoboxes by Liao, Palta and Fillery [12], visual differences in root length and proliferation from the one-leaf stage (10 DAS) were monitored, but it was not until the onset of stem elongation (30 DAS) that significant differences occurred. These findings not only reflect the plasticity of the wheat root system when different cultivars are grown under different conditions [2,15,[38][39][40][41][42][43], but uncover the perils of conducting early-stage root phenotyping in wheat [44,45]. Despite the high plasticity of the root system, wheat cultivars, when grown in the field or in rhizoboxes, maintained a similar ranking in root biomass and root length density under well-watered and moderate water deficit conditions [1,46].…”
Section: Characterising the Root Systems Of Cultivars With Contrastinmentioning
confidence: 80%
“…Although there are examples in which the early stage root phenotype has predictive value for later developmental stages (Tuberosa et al, 2002), the seedling root phenotype may not always be representative of the mature plant (Watt et al, 2013). Because replicate numbers from manual phenotyping of mature root systems are limited but mature root systems often have a higher complexity, adapted statistical methods need to be developed to make full use of data sets.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus evident that each system has its advantages for certain specific applications. Previously, the cultivation of roots on germination paper was used in the form of paper-roll setup (Watt et al 2013) or growth pouches (Hund et al 2009). These studies showed a good correlation with the length of the roots under field conditions in the early stages of growth, but not in the reproductive stage (Watt et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the cultivation of roots on germination paper was used in the form of paper-roll setup (Watt et al 2013) or growth pouches (Hund et al 2009). These studies showed a good correlation with the length of the roots under field conditions in the early stages of growth, but not in the reproductive stage (Watt et al 2013). The length of filter paper in our study was 60 cm, but in principle, an almost unlimited extension is possible as both black filter paper and PVC-P foil are available in rolls.…”
Section: Resultsmentioning
confidence: 99%